Adaptation of Twilight Novel to Film: from Feminism to the Idea of Masculinity - Hidayat, Syarif; Sulaeman, Karina A; Hariyana, Agustinus; Beresaby, Rheinatus A; Suranto, Suranto (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2025)
Adaptation studies are interesting in discussing literary works and films. It is because adapting a scholarly work, like a novel or play, for the big screen is extremely difficult and requires a high level of ability. One of the literary works adapted into a film is the novel Twilight, by Stephanie Meyer. In the adaptation of the novel to the Twilight film, there are many reductions of the story, and additional scenes that are not in the novel. By using the theories of adaptation, feminism, and masculinity, this study analyzes the changes in the theme of feminism in the novel to masculinity in the film, caused by differences in ideas between the novelist and the filmmaker. By applying the comparative method, this study aims to compare the changes in the notion of ​​feminism in the Twilight novel with the idea of ​​masculinity in its film adaptation, and to reveal the motives behind it. The analysis shows that the Twilight film adaptation strategically shifts the feminist themes in the novel version by centering on traditional masculinity, a deliberate choice to appeal to its target audience, particularly teenage girls.